Fatores envolvidos no desenvolvimento e expressão da sensibilização comportamental ao efeito estimulante do modafinil e metanfetamina - Soeiro, Aline da Costa [UNIFESP] (2010)
The behavioral sensitization refers to the progressive increase of the stimulatory effect induced by repeated administration of drugs of abuse such as cocaine and amphetamine. Previous studies suggest that the environment paired with the drug stimulant effect of those drugs has an important role in the behavioral sensitization phenomena. Besides, the chronic treatment with one drug of abuse can induce a different patter of response to the administration of other drug indicating that both drug share some similar mechanism of action. The present study aimed to investigate the involvement of contextual learning in the modafinil and methamphetamine behavioral sensitization phenomena and if there is cross-sensitization between the two drugs. Fifteen days after the contextual fear conditioning task, mice received repeated administration of vehicle or modafinil (50mg/kg - Experiment 2) and saline or methamphetamine (1mg/kg - Experiment 3) for 10 days; they were tested in activity cages on days 1, 5 and 10. To evaluate the expression of behavioral sensitization the mice were challenged with vehicle or modafinil (50mg/kg - Experiment 2) and saline or methamphetamine (1 mg/kg - Experiment 3) and then they were tested in the activity cages and in the open field arena. For cross-sensitization test, mice from Experiment 2 were challenged with saline and methamphetamine (1mg/kg) and those mice from Experiment 3 were challenged with vehicle and modafinil (50mg/kg). In both experiments we did not find any correlation between the levels of freezing in the contextual fear conditioning task and different levels of sensitization. Modafinil-sensitized subgroup of mice expressed clear behavioral sensitization in the activity cage, but not in the open field, suggesting a context-dependent expression of modafinil sensitization. We also observed a symmetric cross-sensitization between modafinil and methamphetamine. Our findings indicate that there are a important individual variability to the development of behavioral sensitization to methamphetamine and to modafinil. Besides, we suggest that modafinil and methamphetamine seem to share similar mechanisms of action.